Accelerated Mutation Accumulation in Asexual Lineages of a Freshwater Snail - Neiman, Maurine (Oxford University Press, 2010)
Sexual reproduction is both extremely costly and widespread relative to asexual reproduction, meaning that it must also confer profound advantages in order to persist. One theorized benefit of sex is that it facilitates the clearance of harmful mutations, which would accumulate more rapidly in the absence of recombination. The extent to which ineffective purifying selection and mutation accumulation are direct consequences of asexuality and whether the accelerated buildup of harmful mutations in asexuals can occur rapidly enough to maintain sex within natural populations, however, remain as open questions. We addressed key components of these questions by estimating the rate of mutation accumulation in the mitochondrial genomes of multiple sexual and asexual representatives of Potamopyrgus antipodarum, a New Zealand snail characterized by mixed sexual/asexual populations. We found that increased mutation accumulation is associated with asexuality and occurs rapidly enough to be detected in recently derived asexual lineages of P. antipodarum. Our results demonstrate that increased mutation accumulation in asexuals can differentially affect coexisting and ecologically similar sexual and asexual lineages. The accelerated rate of mutation accumulation observed in asexual P. antipodarum provides some of the most direct evidence to date for a link between asexuality and mutation accumulation and implies that mutational buildup could be rapid enough to contribute to the short-term evolutionary mechanisms that favor sexual reproduction.